Overuse Knee Injuries in Athletes - Miroslav Kezunović (Montenegrin Journal of Sports Science and Medicine, 2013)
According to many statistics over 55% of all sports-related injuries are incurred in the knee joint (active sportsmen and recreationists). The statistics definitely differ, depending on type of sport and specific movements habitually performed in a particular sport. Therefore, in addition to acute knee injuries overuse syndromes are common in the knee area also due to specificities of patellofemoral joint just because specific diseases like „jumper's knee“ and „runner's knee“ are related to certain sport activities. Generally speaking, these syndromes occur due to poor orientation of the knee extensor mechanism, i.e. friction of iliotibial band and patellofemoral chondromalacia. It is believed that about 45% of all overuse syndromes in the knee area occur as a result of running.